Starchy food residue on a potsherd from a late Holocene hunter-gatherer site in Argentine Patagonia: towards the visibility of wild underground storage organs - Ciampagna, María Laura (2021)
The aim of this paper is to present recent advances in the microbotanical analyses of an organic residue on a potsherd from a late Holocene hunter-gatherer site in Argentine Patagonia, which is the first evidence of this kind for the processing of starchy food. Standard methods were carried out for starch grain recovery and morphometric analysis, care being taken in the prevention of cross-contamination and evaluation of post-depositional factors. Diagnostic features of the ancient starch grains recovered were compared against those from a list, available in the bibliography, of plants potentially processed in pottery, but no match was found. An anatomical and starch grain reference collection was established with three of the most frequently consumed traditional wild underground storage organs (USOs) of Patagonia, Alstroemeria aurea Graham, Tropaeolum porifolium Cav. and Diposis patagonica Skottsb., in order to compare these against the archaeobotanical record. We suggest that T. aff. porifolium (and probably also A. aff. aurea) were processed in the pot from which the sherd came, and discuss these results in terms of a better understanding of the role of wild USOs in subsistence and the possible cooking methods used in hunter-gatherer societies in Argentine Patagonia.